Cognitive ability, self-assessed intelligence and personality : common genetic but independent environmental aetiologies - Bratko, Denis (Array, 2012)
Self-perceived abilities (SPA), which play an important role in academic achievement, have been recently reported to be fully attributable to genetic and non-shared environmental influences. To replicate and extend this finding, 732 Croatian twins (15–22 years old) were assessed on cognitive ability, self-assessed intelligence (SAI), and Five Factor Model personality traits. In addition to attempting to replicate the finding that SAI is due to genetic and non-shared environmental influences, we used bivariate and multivariate genetic analyses to investigate genetic and environmental influences on the phenotypic association of IQ, SAI, and personality traits. The results replicated the finding that individual differences in SAI can be attributed to genetic and non-shared environmental influences. Bivariate and multivariate genetic analyses showed intelligence, SAI measures, and personality traits are inter-correlated not only at the phenotypic but also at the genotypic level. Multivariate analyses indicate that around 20% of IQ variance could be explained by SAI and personality traits (Neuroticism, Extraversion, Openness). In combination with other recent findings from behavior genetics, this result supports the idea of pleiotropy and generalist genes.